Buying and storing food safely - Courcy Browne, Joel de; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2000)
In this program we take a look at this critical issue, covering topics such as buying the best and healthiest items in the supermarket, transporting them home in a safe fashion and safe refrigeration and storage methods
Title from title screen
Executive producer, Neil Barrett, Robyn Holdsworth ; camera, Sasha Trikojus, Walter Repich ; sound, Sue Roberts
Narrator: Gary Newton
Presenter: Helen Highwaters
Keywords: Food -- Storage; Grocery shopping; Food